PRODUCTIVE INTELLIGENCE AS A CONDITION FOR REALIZATION OF THE MODERN EDUCATIONAL PROCESS - Гальченко M. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
In the article the problem of formation of thinking as a way of creation of the person corresponding to socio-cultural demands of the modern world is investigated. There is a need to include the practice of intellectual activity and thinking in the educational and pedagogical process, which allows to activate the formation of worldview and value system. The revealed parameters of the content of productive thinking as a condition of creative activity.